Optimizing Alternative Fumigant Applications for Ornamental Production in Florida - Erin N. Rosskopf; N. Kokalis-Burelle; Robert McSorley; Edward Skvarch (EDIS)
ENY-901, a 6-page illustrated fact sheet by Erin N. Rosskopf, N. Kokalis-Burelle, R. McSorley, and E. Skvarch, presents the results of tests of two alternative fumigants for ornamental production, conducted in Gainesville and Ft. Pierce. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.